Nutritional and Health Benefits of Cereals and Grains - Zaib, Sumera; Hayat, Aqsa; Khan, Imtiaz (Current Nutrition & Food Science, 2024)
The consumption of cereals and grains, along with whole grain food, is considered a healthy food that has various health benefits. Minerals, proteins, carbohydrates, and vitamins are present in the diet of many people. Phytochemicals play an essential role in combating oxidative stress and are present in high amounts in grains. These phytochemicals are also known as secondary metabolites that are present in plants. The nutritional components of basil (Ocimum basilicum), chia (Salvia hispanica), flax (Linum usitatissimmum), Proso millet (Panicum miliaceum), and oat (Avena sativa) are analyzed. Seeds are considered a good source of omega-3 and omega-6 fatty acids that have a significant impact on human health. The high amount of tocopherol (vitamin E) is due to the high content of polyunsaturated fatty acids (PUFAs). γ-Tocopherol is an antioxidant nutrient that usually blocks the formation of carcinogenic nitrosamines from nitrites present in food in the stomach. This review provides detailed information on the nutritional and health benefits of these cereals and grains, in which all the major components have been discussed. Conclusively, the potential use of these cereals and grains alone and by mixing them with other food products is also discussed which may enhance the nutritional content of the food product.
Keywords: Cardiovascular disorders